Crescimento econômico e dívida pública nos países da OECD - Deusdará, Francisca Maria Muniz (2013)
This work was developed with the aim of contributing to the discussion about the impact of the public debt on the economic growth of the OECD countries. Different theoretical and empirical work suggest an effect of economic stagnation when there is an increase in the debt, however, and on the other hand, many authors argue that a rise in the growth strengthens the economy by attracting new investors. There is no consensus in the literature on the subject. This work was developed with the main purpose to provide data that may help clarify the debt and growth paradox. To capture the direction of those two variables as well as the mutual influence of this movement, we used in our study an econometric vector auto-regressive type model – VAR, with annual data from 16 out of the 32 countries considered as advanced economies that make up the Organization for Economic Cooperation and Development – OECD, during the period from 1995 to 2011. The results presented indicate a weak causality going from growth to debt. Thresholds concerning public debt have not been identified. It has been found out that a low economic growth of the countries within the sample, under the Granger sense, causes bigger Debt/GDP ratios.